Identity, social engagement and community participation impact physical activity levels of stroke survivors: A mixed-methods study. (June 2023) - Espernberger, Karl; Fini, Natalie A; Peiris, Casey L
Objective: To explore how personal characteristics and social engagement impact the physical activity levels of chronic stroke survivors. Design: A mixed-methods study comprising in-depth semi-structured interviews and objective 24-h physical activity monitoring. Interviews were thematically analysed, and activity diaries were compared to activity monitor data to attain a complete picture of physical activity. Triangulation explored the relationship between perceptions, beliefs, activity levels and social engagement. Setting: Community. Participants: Community-dwelling, independently mobile, adult stroke survivors (n = 19). The mean age was 74 (11 SD) years, 52% female, mean time post-stroke 41 (SD 61) months. Main measures: Qualitative and quantitative measures including individual semi-structured interviews, accelerometry, activity diaries, self-efficacy, Frenchay Activities Index and Barthel Index. Results: Individual identity had the greatest perceived influence on post-stroke physical activity. Pre-stroke identity, meaningful activities and family culture contributed to identity; while social and community activities, self-efficacy, co-morbidities, stroke symptoms and exercise, also impacted physical activity. Participants averaged 5365 (IQR 3378–7854) steps per day and reported a mean self-efficacy for exercise score of 51 (SD 20). Triangulation showed convergent relationships between post-stroke physical activity levels and participant motivation, comorbidities, level of social and community participation, self-efficacy and pre-stroke activity levels. Conclusion: Personal identity, social engagement and community participation are important factors to consider when implementing a person-centred approach to increasing physical activity participation post-stroke.